2021
DOI: 10.3171/2020.3.jns20389
|View full text |Cite
|
Sign up to set email alerts
|

Near-complete regression 19 years after Gamma Knife radiosurgery of vestibular schwannoma with massive pseudoprogression: case report

Abstract: Gamma Knife radiosurgery (GKRS) is a frequent treatment choice for patients with small- to moderate-sized vestibular schwannoma (VS). However, pseudoprogression after GKRS is commonly observed, with a reported incidence ranging from 7% to 77%. The wide range of the reported incidence of pseudoprogression reflects the fact that there is no consensus on how it should be diagnosed.The authors present the case of a 66-year-old woman who had a 2.5-cm right-sided VS treated with GKRS in 1997… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…It can be challenging to differentiate between true tumor progression and pseudo-progression, in particular, for younger patients, where the threshold of salvage surgery may be lowered, as additional resections are generally tolerable in this age group. Recent studies, in contrast to conventional wisdom, have shown that transient expansion may occur later than 2 years post-SRS and the growth rate may occasionally exceed 50% in volume increase [23][24][25]. Thus, tumors not causing disturbing symptoms or brainstem compression may be amenable to observation despite a certain rate of progression.…”
Section: Discussionmentioning
confidence: 96%
“…It can be challenging to differentiate between true tumor progression and pseudo-progression, in particular, for younger patients, where the threshold of salvage surgery may be lowered, as additional resections are generally tolerable in this age group. Recent studies, in contrast to conventional wisdom, have shown that transient expansion may occur later than 2 years post-SRS and the growth rate may occasionally exceed 50% in volume increase [23][24][25]. Thus, tumors not causing disturbing symptoms or brainstem compression may be amenable to observation despite a certain rate of progression.…”
Section: Discussionmentioning
confidence: 96%
“…Subsequent volumetric measurement is the key to evaluate such progression, while some authors suggested even preradiosurgical radiomics [59]. One should keep in mind that at least 2 years follow-up is usually required [23], avoiding misjudging any temporary tumoral swelling [32]. This should be further judged in the context of presence or absence of patient's symptoms.…”
Section: Discussionmentioning
confidence: 99%